Eksplorasi Penggerek Batang Padi dan Parasitoid di Balai Benih Induk (BBI) Sukajaya - Reno Armando; Yusnaini; Wilma Yunita (Fakultas Pertanian, Universitas Warmadewa, 2020)
This research was conducted with the aim to find out the type of stem borer and the percentage of attack, the type of parasitoid associated with eggs and stem borer larvae. The method used for larval sampling is purposive sampling method, namely deliberate withdrawal. Egg samples are obtained by capturing imago stem borer in the field using a sample bottle then the imago is put into a cage that has been prepared as a place of maintenance to produce eggs. For the purpose of calculating the percentage of stem borer attacks, the location of the sample is determined in rice plantations in the vegetative and generative phases which are spread over 6 planting sites with each location measuring 100 m x 100 m. At each location 5 sample plots were systematically diagonal shaped. Each sample plot consisted of 9 clumps of rice. The results found 5 types of stem borer namely Scirpophaga incertulas Walker, Scirpophaga innotata Walker, Chilo supressalis Walker, Sesamia inferens Walker and Chilo polycrhysus Meyrick. Found 1 type of stem borer parasitoid larvae, namely Stenobracon nicevillei Bingham. Three types of stem borer egg parasitoids were found, namely Tetrastichus schoenobii Ferriere, Telenomus rowani Gahan and Trichogramma japonicum Ashmead. It is known that the percentage of stem borer attacks is 11.94% in the vegetative phase and 11.60% in the generative phase.